A study of ultrasonographic transcerebellar diameter in assessment of fetal gestational age - Mathur, Yashvir; Chauhan, Rahul Dev (International Journal of Research in Medical Sciences, 2018)
Background: Accurate assessment of gestational age is of paramount importance for the clinician to impart holistic antenatal care and is also essential prerequisite to plan the various clinical tests and interventions. Ultrasound (USG) morphometric measurements of fetal parts have been used to assess gestational age of the fetus with improved accuracy. The present study aims at comparing the ultrasonographic measurement of transverse cerebellar diameter (TCD) with other previously established fetal ultrasound biometric parameters, to study its role in patients of suspected intrauterine growth retardation (IUGR) and to study ultrasonographic appearance of fetal cerebellum with advancing gestational age. Methods: A total of 153 pregnant women who were referred for antenatal ultrasound examination were divided into two groups-Group I had 137 healthy pregnant women with normal fetuses between 14-40 weeks of gestation and Group II had 16 patients suspected to have IUGR clinically. Results: In group I, there was a curvilinear relationship between TCD and BPD, TCD and HC, TCD and AC and TCD and FL with correlation coefficients being 0.9810, 0.9181, 0.9649 and 0.9513 respectively. In group II, TCD correlated with gestational age predicted by last menstrual period. The remaining biometric parameters in group-II predicted a fetus of much earlier grade. The study findings also suggested a gradual and steady change in ultrasonographic appearances of cerebellum with advancing gestation. Conclusions: Ultrasonographic measurement of TCD shows excellent correlation with advancing gestational age and with other previously established biometric parameters. TCD can serve as an independent and reliable indicator of gestational age and a standard against which aberrations in fetal growth may be compared.